FACTORS ASSOCIATED WITH DEPRESSION AMONG RESIDENTS OF ELDERLY NURSING HOMES IN SABAH - Mohd Idrus, Idzhar Azwan; Robinson, Fredie; Mohamed, Noor Hassline (Malaysian Journal of Public Health Medicine, 2025)
Mental health has become an increasingly important public health issue, especially with the growing elderly population. Depression is common among older adults, especially those living in long-term care facilities, where social and emotional needs are often overlooked. This study aimed to determine factors associated with depression among elderly nursing home residents in Sabah, Malaysia. A cross-sectional study was conducted among 169 residents from three government and five private elderly nursing homes. Purposive sampling was used, and trained enumerators assisted participants during data collection. The instruments used were the Geriatric Depression Scale, Mini-Mental State Examination, Rosenberg Self-Esteem Scale, Oxford Happiness Questionnaire, and Satisfaction with Life Scale. Sociodemographic data, such as age, gender, ethnicity, marital status, and length of stay, were also collected. Multiple logistic regression analysis was used to identify predictors of depression. The prevalence of abnormal depression levels was 82.8%. Low self-esteem [AOR=4.00 (1.17, 13.63)] and reduced happiness [AOR=3.44 (1.02, 11.55)] were significantly associated with depression. The findings indicate that psychological well-being, particularly self-esteem and happiness, plays a crucial role in elderly mental health. Interventions should therefore emphasise enhancing self-worth, promoting social engagement, and fostering positive emotions through structured recreational programmes tailored to the cultural and emotional needs of residents. Strengthening these aspects within elderly care services could help reduce depressive symptoms and support healthy ageing among institutionalised older adults in Sabah.